Penerapan Strategi Peta Konsep untuk Meningkatkan Kemampuan Menulis Materi Teks Deskripsi Siswa MTs. Ubbbadussomad NW Kalijaga Selatan Kelas VIII TA.2025/2026 - Arina, NurFathil Maula; Intiana, Siti Rohana Hariana; Susanti, Pipit Aprilia; Mahyudi, Johan (STKIP Singkawang, 2025)
This research aims to improve the descriptive text writing skills of eighth-grade students at MTs Ubbadusshomad DS NW Kalijaga Selatan in the academic year 2025/2026 through the application of the concept map method. This study employed Classroom Action Research (CAR), conducted in one cycle with two meetings. The research subjects consisted of 18 students. Data were collected through observation, writing tests, and documentation, and were analyzed both quantitatively and qualitatively.The results revealed that the implementation of the concept map method successfully enhanced students. ability to write descriptive texts. This was evident from the average score at the end of the cycle, which reached 81.94, with a 100% mastery level, indicating that all students exceeded the Minimum Mastery Criteria (KKM) of 75. Qualitatively, students became more skilled in organizing ideas, constructing sentences, and applying the structure of descriptive texts. Therefore, the concept map method is proven to be effective in teaching Indonesian language, particularly in improving students descriptive writing skills.